Sistem Informasi Manajemen Pelayanan Service Berbasis Web pada Efox tech - Masikhoh, Laili; Kasoni, Dian; Subhiyanto (LPPM STMIK ANTAR BANGSA, 2025)
Abstract— Efox Tech faces customer management challenges due to manual record-keeping. Issues include slow response times, incomplete device data, risk of device mix-ups, unclear repair status, and inaccurate financial records. To improve efficiency, Efox Tech plans to implement a web-based management system that allows customers to request services, track repair status, and communicate with technicians. This system will streamline record-keeping, enhance financial transparency, and improve service quality.